Katerina Ragkou, Eastern Mediterranean Economic Networks in the Age of the Crusades: The Case of the Peloponnese - ΤΣΟΥΓΚΑΡΑΚΗΣ (Nikiforos-Ioannis TSOUGARAKIS), Νικηφόρος-Ιωάννης (Δελτίον της Χριστιανικής Αρχαιολογικής Εταιρείας, 2023)
Katerina Ragkou, Eastern Mediterranean Economic Networks in the Age of the Crusades: The Case of the Peloponnese (Studies in Mediterranean Archaeology and Literature PB 189), Ảström Editions, Nicosia 2020, XIV+198 σ. Περιλαμβάνεται βιβλιογραφία στις σ. 159-198. ISBN: 9789925745579.